Effect of Porosity on Uniaxial Compressive Strength in Sedimentary Rocks - Andesta Granitio Irwan (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2020)
The rock strength parameter is an important factor used in determining the geotechnical design in determining the stability of the underground slope or mine. One of the rock strength tests in the laboratory (intact rock) is the uniaxial compressive strength test. One of the factors that influence rock strength is the porosity of the rock itself, especially in sedimentary rocks. The rock porosity test is carried out by testing the physical properties of the rock, then a regression analysis is carried out to obtain the correlation of the effect of porosity on rock strength and the correlation between porosity and absorption considered in the analysis. The linear regression results obtained between porosity and saturated water content of rocks showed a positive correlation where the increase in porosity, the saturated water content also increased. The correlation between porosity and uniaxial compressive strength obtained a strong correlation with the power regression model as the best model compared to other regression models because it has the lowest error based on the Root Mean Square Error (RMSE). The final result is obtained by comparing the effect of porosity on rock strength, that is the higher the porosity value have the smaller porosity, so that an increase in rock porosity will reduce the strength of the rock.